Exploring Facebook as an online support group for smoking cessation - Ashley, Stephanie, author; Long, Marilee, advisor; Rouner, Donna, committee member; Broadfoot, Kirsten, committee member (Colorado State University. Libraries, 2012)
This paper employed a quantitative content analysis of the messages posted to a public Facebook page about smoking cessation. The study's population consisted of posts from October and November of 2010, from which a two-week constructed sample was drawn. The sample yielded 118 threads made up of 344 individual posts for analysis. Within the sample, 98 individuals (35 men, 54 women, 9 unidentifiable) served as the unit of analysis. This research explored the types of messages posted on Facebook to see if participants acted in line with gender norms for communicating online and about health. The types of support explored through the posts were informational, esteem and emotional. Results showed that men and women acted differently on the page than traditional gender norms would predict. Specifically, men and women posted to the page at similar rates and both groups used informational support more often than esteem support or emotional support. Smoking status was related to page use; the most active individuals posting to the page were recent quitters and they had a tendency to use informational and esteem support more often than emotional support. Participants also used Facebook's "like" function more often than posting messages containing overt support.
Keywords: Facebook; support; smoking cessation; health; gender communication